2000
DOI: 10.1007/s005400050003
|View full text |Cite
|
Sign up to set email alerts
|

What is the optimal dose of glucose administration during minor surgery under sevoflurane anesthesia?

Abstract: The smaller doses of glucose (0.1-0.2 g.kg(-1).h(-1)) prevented lipolysis and hyperglycemia during minor surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…To assess the effects of glucose infusion on insulin resistance after surgery, further study is needed. During surgery, it has been reported that infusion of 0.1 g glucose/kg BW/h has positive effects, including preventing glycogen depletion 30 and preventing lipolysis and ketosis, 40 and these effects are not dose-dependent. Con-sidering all of these findings, a low-rate glucose infusion of 0.1 g • kg -1 • h -1 appears to have clinical potential to suppress muscle protein breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effects of glucose infusion on insulin resistance after surgery, further study is needed. During surgery, it has been reported that infusion of 0.1 g glucose/kg BW/h has positive effects, including preventing glycogen depletion 30 and preventing lipolysis and ketosis, 40 and these effects are not dose-dependent. Con-sidering all of these findings, a low-rate glucose infusion of 0.1 g • kg -1 • h -1 appears to have clinical potential to suppress muscle protein breakdown.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we noticed that in the intervention group, providers co-administered dextrose (5 % at 100 ml/ Hr) with insulin in significantly more number of cases when compared with the baseline (68.4 % for intervention when compared with 54 % for baseline). Co-administration of dextrose with insulin is recommended by the UW protocol to minimize catabolic effect in fasting surgical patients [40]. In compliance with this recommendation SAM prompts providers to co-administer dextrose with insulin (Rule GLU5 in Table 1).…”
Section: Discussionmentioning
confidence: 95%
“…Unlike anesthesia with propofol and an opioid analgesic (sufentanil, fentanyl), anesthesia with a volatile gas (enflurane, isoflurane, sevoflurane) cannot sufficiently block the invasiveness of surgery, which leads to elevated plasma cortisol levels and a failure to sufficiently suppress the endocrine stress response [2629]. Administering glucose to a patient under these conditions suppresses lipid and protein catabolism, but tends to cause exaggerated hyperglycemia [3,4,15,16]. Anesthesia with fentanyl or remifentanil, on the other hand, suppresses the stress response and reduces ACTH and cortisol levels regardless of the extent of surgery, and, thus, inhibits lipid mobilization without triggering hyperglycemia following low-dose glucose administration [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…The stress response of the endocrine and metabolic systems to the insult of surgery lowers insulin secretion, which in turn lowers insulin sensitivity, increases the release of catabolic hormones, reduces glucose utilization, and increases gluconeogenesis, thus increasing blood glucose levels [1316]. Many studies have found that administration of low-dose glucose solutions during surgery, on the other hand, suppresses the level of blood ketone bodies and free fatty acids (FFAs) without substantially increasing blood glucose levels, and also increases insulin levels [3,4,13,14,17].…”
Section: Introductionmentioning
confidence: 99%